Monomeric C-Reactive Protein Localized in the Cerebral Tissue of Damaged Vascular Brain Regions Is Associated With Neuro-Inflammation and Neurodegeneration-An Immunohistochemical Study - Al-Baradie, Raid S.; Pu, Shuang; Liu, Donghui; Zeinolabediny, Yasmin; Ferris, Glenn; Sanfeli, Coral; Corpas, Ruben; Garcia-Lara, Elisa; Alsagaby, Suliman A.; Alshehri, Bader M.; Abdel-hadi, Ahmed M.; Ahmad, Fuzail; et al. (Frontiers in Immunology, 2021)
In the last decade we and others have previously showed the importance of mCRP in the induction of inflammation and in addition, the prevalence of the monomeric C-reactive protein (mCRP) form in the brains of individuals with dementia, after ischaemic stroke and following other brain vascular damage or degeneration. Since neuroinflammation may be a key trigger/cause of later dementia, here we carried out an IHC study on a small cohort of brain samples, using a monoclonal (8C10 clone) highly specific anti-mCRP antibody to investigate its expression in vascular regions of damage highlighting the associated tissue morphology. We showed that mCRP was present in specific brain regions with medium sized cerebral vessels showing high intraluminal content that was associated with leakage and transport into the local tissue. Where this occurred, cells with the morphology of neurones, macrophages and glia, as well as smaller microvessels became mCRP-positive in regions staining for the inflammatory markers CD68 (macrophage), interleukin-1 beta (IL-1β) and nuclear factor kappa B (NFκB), showing evidence of a perpetuation of inflammation. Positive staining was seen even in distant hypothalamic regions. Co-staining of cells with p-Tau and B-amyloid indicated a relationship as shown by us and others previously with neurogenerative processes. In conclusion, vascular injury or leakage from any cause appears to be associated with mCRP accumulation and leakage into brain tissue and this could be a critical element associated with enhanced neuroinflammation and later neurodegeneration and dementia.